THE ROLE OF LEADERSHIP, TRAINING AND SURVEILANCE ON EMPLOYEES’ JOB PERFORMANCE - Windayani Zakaria Sapan; Junaidi Junaidi; M. Yusuf Qamaruddin; Andi Nadhirah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Strong and inspiring leadership significantly enhances the commitment of the employee of government (ASN) locally and globally; a leader who is able to give clear directions, motivate, and be an example can cultivate a sense of responsibility and loyalty to ASN. Moreover, effective leadership directly contributes to improved ASN performance. The objectives of the study are to identify the impacts of leadership styles, training, and organizational surveillance on employees’ job performance. This study included 211 employees from the financial department in the Luwu Timur regency and employed structural equation modelling (SEM) to investigate the research hypotheses. The Hayes bootstrapping approach examined employee commitment as a mediator variable. The empirical findings demonstrate that leadership and training have a positive and significant impact on organizational surveillance quality, both directly and indirectly, leading to an increase in employees’ job performance. The government should establish clear rules and laws to uphold the job standard, thereby enhancing public trust and increasing government credibility. Furthermore, training can help ASN work more efficiently and productively. High work controling is also closely linked to improved ASN performance; ASNs that adhere to established work schedules, procedures, and standards can complete tasks better and on time.